Health outcomes in redlined versus non-redlined neighborhoods: A systematic review and meta-analysis. (February 2022) - Lee, Eun Kyung; Donley, Gwendolyn; Ciesielski, Timothy H.; Gill, India; Yamoah, Owusua; Roche, Abigail; Martinez, Roberto; Freedman, Darcy A.
Abstract: Background: Redlining was a racialized zoning practice in the U.S. that blocked fair access to home loans during the 1930s, and recent research is illuminating health problems in the current residents of these historically redlined areas. However, this work has not yet been holistically summarized. Here, we present the first systematic review and meta-analysis comparing health outcomes in redlined versus non-redlined neighborhoods in U.S. cities. Methods: We extracted relevant articles in PubMed, Web of Science, Cochrane and Science Direct databases published from January 2010 to September 2021. Results: The search revealed 12 studies on preterm births (n = 3), gunshot-related injuries (n = 2), cancer (n = 1), asthma (n = 1), self-rated health (n = 1), multiple health outcomes (n = 2), heat-related outcomes (n = 1) and COVID-19 incidence and mortality (n = 1). A meta-analysis of three studies found the odds of having preterm birth was significantly higher (OR = 1.41, 95% CI: 1.05, 1.88; p = 0.02) among women living in redlined areas compared to those in non-redlined areas. Review of other outcomes revealed that gunshot-related injuries, asthma, heat-related outcomes, and multiple chronic conditions were worse in redlined areas, while associations with cancer varied by cancer type. In terms of cause-specific mortality, one study revealed no link between residential redlining and infant mortality rate, while one study on COVID-19 outcomes was inconclusive. Conclusions: Overall, this review presents evidence that living in historically redlined areas is associated with increased risk of multiple serious adverse health outcomes. Further research on mechanisms, remediation, and neighborhood-level interventions is needed to strengthen the understanding of the impacts of redlining on health. Highlights: First systematic review to examine the relationships between redlining and modern-day health inequities. Residential redlining is associated with elevated risk for multiple chronic diseases. Future research focusing on community-level interventions and policies may be informative and impactful. Standardization of design and measurement of redlining is needed.